2020
DOI: 10.1101/2020.09.01.277822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gradual development of non-adjacent dependency learning during early childhood

Abstract: In order to become proficient native speakers, children have to learn the grammatical rules of their language. These grammatical rules can define morpho-syntactic relations between neighboring as well as distant elements of a sentence, so-called non-adjacent dependencies (NADs). Previous neurophysiological research suggests that NAD learning comprises different developmental stages during early childhood. Children up to 2 years of age show evidence of associative NAD learning under passive listening conditions… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
(137 reference statements)
0
3
0
Order By: Relevance
“…The question arises as to whether the capacity for a more associative bottom-up learning from passive listening ends abruptly around the age of 3 years or whether it might gradually be replaced by a more top-down, controlled learning mechanism. Paul et al (2020) investigated this transition of NAD learning and collected ERP data from children between 1 and 3 years of age. Using the same experimental paradigm as in the above cited studies ( Mueller et al, 2009 ; Citron et al, 2011 ; Friederici et al, 2011 ) they observed that the amplitude of the ERP effect of NAD learning decreased linearly with age suggesting a gradual decrease of NAD learning from passive listening.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The question arises as to whether the capacity for a more associative bottom-up learning from passive listening ends abruptly around the age of 3 years or whether it might gradually be replaced by a more top-down, controlled learning mechanism. Paul et al (2020) investigated this transition of NAD learning and collected ERP data from children between 1 and 3 years of age. Using the same experimental paradigm as in the above cited studies ( Mueller et al, 2009 ; Citron et al, 2011 ; Friederici et al, 2011 ) they observed that the amplitude of the ERP effect of NAD learning decreased linearly with age suggesting a gradual decrease of NAD learning from passive listening.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same experimental paradigm as in the above cited studies ( Mueller et al, 2009 ; Citron et al, 2011 ; Friederici et al, 2011 ) they observed that the amplitude of the ERP effect of NAD learning decreased linearly with age suggesting a gradual decrease of NAD learning from passive listening. Importantly, Paul et al (2020) argued on the one hand for a developmental shift, presumably influenced by maturation of the prefrontal cortex (PFC) and other neuronal circuits ( Skeide and Friederici, 2016 ), but on the other hand also proposed that children’s knowledge and entrenchment of their native language has an influence on the changes in their learning outcomes. According to Skeide and Friederici (2016) , when maturation has reached a certain degree, top-down control increasingly takes effect, which in turn inhibits associative bottom-up learning mechanisms, also limiting the ability to learn NADs under passive listening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation